Altered Maturation of Medullary TEC in EphB-Deficient Thymi Is Recovered by RANK Signaling Stimulation - Montero-Herradón, Sara; García-Ceca, Javier; Zapata, Agustín G. (Frontiers in Immunology, 2018)
In the present study, the relevance of EphB2 and EphB3 tyrosine kinase receptors for the maturation of medullary thymic epithelial cells is analyzed. The absence of both molecules, but particularly that of EphB2, courses with altered maturation of medullary Cld3,4hiSSEA1+ epithelial progenitor cells, mature medulla epithelial cells, defined by the expression of specific cell markers, including UEA1, MHCII, CD40, CD80 and AIRE, and reduced expansion of medullary islets. In vivo assays demonstrate that these changes are a consequence of the absence of EphBs in both thymic epithelial cells and thymocytes. On the other hand, the changes, that remains in the adult thymus, correlated well with reduced proportions of E15.5 Vγ5+RANKL+ cells in EphB-deficient thymi that could result in decreased stimulation of RANK+ medullary thymic epithelial cells to mature, a fact that was confirmed by recovering of proportions of both CD40hiCD80+ and MHCIIhiUEA1+ mature medullary thymic epithelial cells of mutant E14.5 alymphoid thymic lobes by agonist anti-RANK antibody treatment. Accordingly, the effects of EphB deficiency on medullary thymic epithelial cells maturation are recovered by RANK stimulation.